Repositioning the boundaries between public and private healthcare providers in the English NHS. Issue 7 (7th November 2019) - Sheaff, Rod; Halliday, Joyce; Exworthy, Mark; Gibson, Alex; Allen, Pauline W.; Clark, Jonathan; Asthana, Sheena; Mannion, Russell
Abstract : Purpose: Neo-liberal "reform" has in many countries shifted services across the boundary between the public and private sector. This policy re-opens the question of what structural and managerial differences, if any, differences of ownership make to healthcare providers. The purpose of this paper is to examine the connections between ownership, organisational structure and managerial regime within an elaboration of Donabedian's reasoning about organisational structures. Using new data from England, it considers: how do the internal managerial regimes of differently owned healthcare providers differ, or not? In what respects did any such differences arise from differences in ownership or for other reasons? Design/methodology/approach: An observational systematic qualitative comparison of differently owned providers was the strongest feasible research design. The authors systematically compared a maximum variety (by ownership) sample of community health services; out-of-hours primary care; and hospital planned orthopaedics and ophthalmology providers ( n =12 cases). The framework of comparison was the ownership theory mentioned above. Findings: The connection between ownership (on the one hand) and organisation structures and managerial regimes (on the other) differed at different organisational levels. Top-level governance structures diverged by organisational ownership and objectives among the case-study organisations. All the case-study organisations irrespective of ownership had hierarchical, bureaucratic structures and managerial regimes for coordinating everyday service production, but to differing extents. In doctor-owned organisations, the doctors', but not other occupations', work was controlled and coordinated in a more-or-less democratic, self-governing ways. Research limitations/implications: This study was empirically limited to just one sector in one country, although within that sector the case-study organisations were typical of their kinds. It focussed on formal structures, omitting to varying extents other technologies of power and the differences in care processes and patient experiences within differently owned organisations. Practical implications: Type of ownership does appear, overall, to make a difference to at least some important aspects of an organisation's governance structures and managerial regime. For the broader field of health organisational research, these findings highlight the importance of the owners' agency in explaining organisational change. The findings also call into question the practice of copying managerial techniques (and "fads") across the public–private boundary. Originality/value: Ownership does make important differences to healthcare providers' top-level governance structures and accountabilities and to work coordination activity, but with different patterns at different organisational levels. These findings have implications for understanding the legitimacy, governance and accountability of healthcare organisations, the distribution and use power within them, and system-wide policy interventions, for instance to improve care coordination and for the correspondingly required foci of healthcare organisational research.